2011
DOI: 10.3109/19401736.2011.636440
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the red-spotted tokay gecko (Gekko gecko, Reptilia: Gekkonidae): Comparison of red- and black-spotted tokay geckos

Abstract: Here, we sequenced the complete mitochondrial genome of the red-spotted tokay gecko (Squamata: Gekkonidae). The genome is 16,590 bp in size. Its gene arrangement pattern was identical with that of black-spotted tokay gecko. We compared the mitochondrial genome of red-spotted tokay gecko with that of the black-spotted tokay gecko. Nucleotide sequence of the two whole mitochondrial genomes was 97.99% similar, and the relatively high similarity seems to indicate that they may be separated at the subspecies level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Taken together with our study and several morphological, behavioral, and genetic studies as discussed above (Zhang et al, 1997;Yu et al, 2000Yu et al, , 2011Yuan and Li, 2008;Qin et al, 2009Qin et al, , 2011Peng et al, 2010Peng et al, , 2011Gu et al, 2011;Rö sler et al, 2011;Wang et al, 2012), we proposed that the black tokay from southern China should be regarded as a species. Besides the possible taxonomic division between the black tokay and the red tokay, three relatively deeply divergent lineages of the red tokay (Subclade A2, Clade B, and Clade C) were revealed in the phylogenetic tree.…”
Section: Taxonomic Considerationsupporting
confidence: 85%
See 1 more Smart Citation
“…Taken together with our study and several morphological, behavioral, and genetic studies as discussed above (Zhang et al, 1997;Yu et al, 2000Yu et al, , 2011Yuan and Li, 2008;Qin et al, 2009Qin et al, , 2011Peng et al, 2010Peng et al, , 2011Gu et al, 2011;Rö sler et al, 2011;Wang et al, 2012), we proposed that the black tokay from southern China should be regarded as a species. Besides the possible taxonomic division between the black tokay and the red tokay, three relatively deeply divergent lineages of the red tokay (Subclade A2, Clade B, and Clade C) were revealed in the phylogenetic tree.…”
Section: Taxonomic Considerationsupporting
confidence: 85%
“…By analyzing Cyt b genes of the black tokay and the red tokay from China, Vietnam, and Laos, Qin et al (2007) found that the average divergence between the two tokays was 8.6 -9.5% and thus proposed that these two tokays might had been separated at the subspecies level or species level. This subspecies conclusion was further confirmed by analyzing two complete mitochondrial genomes from a black tokay and a red tokay (Qin et al, 2011). In addition to the divergence in mitochondrial DNA, microsatellite DNA had already demonstrated that these two tokays were genetically different (Peng et al, 2010.…”
Section: Introductionmentioning
confidence: 74%
“…Whole mitochondrial genome of L. agilis was amplified with 15 pairs of primers and was completely sequenced by experimental protocols that are routinely used in a laboratory (Qin et al, 2011). The complete mitochondrial genome of L. agilis consists of 17,090 bp (GenBank accession number: KC990830) and including 13 protein coding genes (PCGs), 2 rRNA genes and 22 tRNA genes, and a non-coding control region (D-loop).…”
mentioning
confidence: 99%
“…Black-spotted Tokay Geckos are the authentic medical material while red-spotted Tokay Geckos are a substitute [1,44]. Numerous studies show signi cant differences between the blackspotted and red-spotted Tokay Geckos based on vocalization analyses, 12S rRNA gene sequences, complete mitochondrial genome and mitochondrial cytochrome b gene sequences, nuclear DNA information, karyotypes, and microsatellite loci analyses [45,[46][47][48][49][50]. Furthermore, Qin, Zhang, and Kongbuntad found that G. gecko were genetically diverse in relation to their geographical distribution [51][52][53].…”
Section: Discussionmentioning
confidence: 99%